Hard clam relocation as a potential strategy for QPX disease mitigation within an enzootic estuary. (11th May 2015) - Dahl, Soren F; Allam, Bassem
Abstract: Monitoring of persistent QPX infections in clams of Raritan Bay (New York) shows certain areas of the estuary have remained without any significant disease prevalence. This study was conducted to investigate the potential to mitigate QPX disease by relocating infected hard clams, Mercenaria mercenaria (Linnaeus), from enzootic areas to nearby sites with prevailing environmental conditions suggested to deter infection and favour remission and healing. Clams were collected from a location with consistent disease prevalence in central Raritan Bay and brought to near shore habitats subject to lower salinities and higher summer temperatures. A reduced host density treatment was included in the study to examine the common observation of high clam density in the most persistently infected locales. An additional treatment retained clams above the sediment, since sediments are suspected to represent a QPX reservoir. At the end of the 4‐month study all treatments displayed less QPX disease than the control group and the greatest contrast was provided by the disappearance of infections in a tidal creek.